Analysis of marine solar power trials on Blue Star Delos. Issue 3 (1st September 2016) - Atkinson, Gregory Mark
ABSTRACT: In October 2014 the high speed car and passenger ferry Blue Star Delos was fitted with a marine solar power system. This was done as part of a project to study the use of renewable energy on large ships. In May 2015 while the ship operated in the Aegean Sea, the performance of system was checked and a range of data collected. This paper is focused on the analysis of these data and the evaluation of two days of system trials.